Comment on Energy Spectrum of a Dirac Particle with Position-Dependent Mass Under the Influence of the Aharonov-Casher Effect - Mendrot, V. B. [UNESP]; Castro, A. S. de [UNESP] (Springer, 2020)
It is shown that the paper Energy spectrum of a Dirac particle with position-dependent mass under the influence of the Aharonov-Casher effect, by Oliveira et al. (Braz. J. Phys. 49, 801 2019), is based on a series of ingredients clearly incorrect.
Keywords: Dirac particle; Position-dependent mass; Chirality; (2+1)-dimensional world